Determination of withdrawal times in individualized opportunistic screening colonoscopies - Zhan, Qiang (2019)
To investigate effects of bowel preparation, experience level of colonoscopists, and colonoscopy withdrawal time (CWT) on the quality of an individual opportunistic screening colonoscopy, according to adenoma detection rate (ADR).Data were retrospectively analyzed from opportunistic screening colonoscopies (n = 16,951) at 4 hospitals of various care levels in China.The ADR positively correlated with the experience level of the colonoscopist. The individualized CWT varied, depending on the quality of bowel preparation and the number of colonoscopies performed previously by the colonoscopist. In a setting of adequate bowel preparation, the mean CWT decreased with the increased experience of the colonoscopist. With poor and inadequate bowel preparation, no colonoscopist at any level of experience could obtain a satisfactory ADR.For adequately prepared colonoscopies, minimum CWTs have been determined. Repeat colonoscopy is strongly recommended for patients with poor bowel preparation, regardless of the colonoscopist's experience.